Influence of musculoskeletal pain on workers' ergonomic risk-factor assessments. (July 2015) - Chiasson, Marie-Ève; Imbeau, Daniel; Major, Judy; Aubry, Karine; Delisle, Alain
Abstract: This study compares the ergonomic risk-factor assessments of workers with and without musculoskeletal pain. A questionnaire on the musculoskeletal pain experienced in various body regions during the 12 months and seven days preceding the data collection was administered to 473 workers from three industrial sectors. The Ergonomic Workplace Analysis method, developed by the Finnish Institute of Occupational Health (FIOH), was then used by the workers and an ergonomics expert to assess the workstations. The ergonomic quality of the workstations and the need for change were also assessed by the expert and the workers at the workstation, using visual analog scales (VAS). Results show that the workers in this study were exposed to significant musculoskeletal disorder (MSD) risk factors, according to the FIOH assessment and the high percentages of reported pain. The results also show that those who reported pain in the seven days prior to the assessment evaluated their workstations more negatively than subjects who reported no pain, while the expert found no difference between the two groups' exposure to MSD risk factors. Highlights: This study compares the workstation assessments of workers with and without musculoskeletal pain. Workers reporting pain assessed their workstations more negatively with respect to certain aspects related to ergonomic risk factors. Findings indicate that from an MSD prevention point of view, an ergonomics expert assessment may be more suitable to detect at risk workstations.